2022
DOI: 10.3390/cancers14122828
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of Zeste Homolog 2 (EZH2) Is a Marker of High-Grade Neuroendocrine Neoplasia in Gastroenteropancreatic and Pulmonary Tract and Predicts Poor Prognosis

Abstract: Tumor grading is a robust prognostic predictor in patients with neuroendocrine neoplasms (NEN) and guides therapy, especially in tumors with high proliferation. NEN can be separated into well-differentiated and poorly differentiated types. The more aggressive NEN have been further separated into neuroendocrine tumors (NET G3) with a better prognosis and neuroendocrine carcinomas (NEC) with a worse prognosis. Despite this distinction’s tremendous clinical and therapeutic relevance, optimal diagnostic biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Liverani et al found that DLL3 is expressed in poorly differentiated NEC but not in NET G3 and is associated with poor prognosis. They concluded that DLL3 is considered to serve as a NEC diagnostic marker and potential therapeutic target (21). Bremer et al similarly used immunohistochemistry to find that high expression of Enhancer of Zeste Homolog 2 (EZH2) in high-grade NENs was associated with poorer OS and was also significantly correlated with histological manifestations of NEC, proposing that EZH2 could be used as a biomarker to differentiate NET G3 from NEC (22).…”
Section: Discussionmentioning
confidence: 99%
“…Liverani et al found that DLL3 is expressed in poorly differentiated NEC but not in NET G3 and is associated with poor prognosis. They concluded that DLL3 is considered to serve as a NEC diagnostic marker and potential therapeutic target (21). Bremer et al similarly used immunohistochemistry to find that high expression of Enhancer of Zeste Homolog 2 (EZH2) in high-grade NENs was associated with poorer OS and was also significantly correlated with histological manifestations of NEC, proposing that EZH2 could be used as a biomarker to differentiate NET G3 from NEC (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that enhancer of zeste homolog 2 (EZH2) serves as a key component of polycomb repressive complex 2 (PRC2) (12). EZH2 serves a role in chromosomal structure formation, cell cycle regulation, senescence, cell differentiation and promotion of tumor growth and metastasis in malignant tumor models (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%